2013
DOI: 10.1177/0956797613475632
|View full text |Cite
|
Sign up to set email alerts
|

Learned Control Over Distraction Is Disrupted in Amnesia

Abstract: Recent studies have demonstrated that brief periods of training facilitate the ability to overcome distraction upon future encounters with a given task, and these effects have been proposed to rely on relational memory systems that enable individuals to link specific attentional states to their learned context. In the current work we examined whether medial temporal lobe (MTL) structures critical for relational and contextual learning participate in driving these effects. A group of amnesic patients with bilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…Recent studies showing that there are polysynaptic pathways linking hippocampal and oculomotor circuitry (Ryan et al, ; Shen, Bezgin, Selvam, McIntosh, & Ryan, ) provide a concrete neuroanatomical basis for hippocampal involvement in inhibition of return. Studies of people with medial temporal lobe damage that have revealed the importance of human hippocampal circuitry for some attention‐related phenomena (e.g., Chun & Phelps, ; Cosman & Vecera, ) provide one methodological model for how such an involvement might be explored.…”
Section: How Might Spontaneous Alternation and Inhibition Of Return Fmentioning
confidence: 99%
“…Recent studies showing that there are polysynaptic pathways linking hippocampal and oculomotor circuitry (Ryan et al, ; Shen, Bezgin, Selvam, McIntosh, & Ryan, ) provide a concrete neuroanatomical basis for hippocampal involvement in inhibition of return. Studies of people with medial temporal lobe damage that have revealed the importance of human hippocampal circuitry for some attention‐related phenomena (e.g., Chun & Phelps, ; Cosman & Vecera, ) provide one methodological model for how such an involvement might be explored.…”
Section: How Might Spontaneous Alternation and Inhibition Of Return Fmentioning
confidence: 99%
“…Many studies have demonstrated that when participants are instead encouraged to search for a specific shape (called feature-search mode ), salient stimuli no longer capture covert attention (Bacon & Egeth, 1994; Cosman & Vecera, 2013; Leber & Egeth, 2006) or overt attention (Leonard & Luck, 2011; Theeuwes et al, 2003; Wu & Remington, 2003). For example, Leonard and Luck (2011) had participants perform an additional singleton paradigm, as described above.…”
Section: Suppression Of Overt Attentional Capture By Salient Stimulimentioning
confidence: 99%
“…These findings suggest that parietal areas may be engaged along with memory regions to control the expression of WM biases, which are otherwise triggered through the frontothalamic pathway and linked the temporal and visual cortices. Hippocampal engagement has been found in this form of attention guidance by long-term memory experience (Greene, Gross, Elsinger, & Rao, 2007;Cosman & Vecera, 2013;Summerfield, Lepsien, Gitelman, Mesulam, & Nobre, 2006;Stokes, Atherton, Patai, & Nobre, 2012), which likely reflects the recall of the spatial layout of target objects within the current scene (Chun & Phelps, 1999). Neither of these substrates has form part of the neural circuitry of attention control in current models (Desimone & Duncan, 1995;Petersen & Posner, 2012) yet emerging evidence has began to illustrate their contribution.…”
Section: Brain Substrates For Strategic Control Of Wm Biasesmentioning
confidence: 99%